DEVELOPMENT OF THE ELECTRONIC TAFSEER IN INDONESIA: DESCRIPTION OF TALKING PEN MUSHAF GRAND MAQAMAT - Rohmatun, Taaibah Ngaunillah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
Recently, there have been many applications or features for interpreting the Qur'an in electronic media, such as the E-Pen. One application or feature of the interpretation of the Qur'an that is quite good is the Grand Maqamat Mushaf. This Grand Maqamat Mushaf offers many quite sophisticated features in reading and recitation. This article aims to examine and explore the Grand Maqamat Mushaf, its features, presentation of interpretations, and also its advantages and disadvantages. Using descriptive-analytical analysis of McLuhan's theory, the researchers concluded that the Talking Pen Mushaf Grand Maqamat has several features to make it easier to read, understand, and learn the Qur'an features such as translation, interpretation, the reason for the revelation (asbāb an-nuzūl) of the Qur'an, and related hadiṡ. In addition, Pen Mushaf Grand Maqamat is also equipped with readings from various stations, making it easier for Qori to learn to distinguish tones or sounds from several stations. However, it should also be noted that any sophisticated technology has advantages or disadvantages.